COVID-19 - Ryan, J. Michael (Routledge, 2021)
The SARS-CoV-2 virus, commonly referred to as COVID-19, is perhaps the greatest threat to life, and lifestyles, around the world in more than a century. Although there is little global agreement on many issues related to the virus, there is widespread agreement that the actual number of cases – both of those infected and of those who have died as a result of infection – is certainly much higher than official numbers suggest. The impact of the virus, however, has spread well beyond the realm of the medical, also heavily impacting social, cultural, economic, political, and quotidian ways of living for nearly every human being on the planet. The two edited volumes in this set contribute to a broader understanding of the impact COVID-19 is having, and will have, on our understandings, efforts, and decisions of the future of global society.
Keywords: Pandemie; Auswirkung; COVID-19; Ideologie; Kulturwandel; Gesellschaft; Aufsatzsammlung